Complete Freund's adjuvant induces experimental autoimmune myocarditis by enhancing IL‐6 production during initiation of the immune response. Issue 2 (13th March 2017) - Fontes, Jillian A.; Barin, Jobert G.; Talor, Monica V.; Stickel, Natalie; Schaub, Julie; Rose, Noel R.; Čiháková, Daniela
Abstract: Introduction: Complete Freund's Adjuvant (CFA) emulsified with an antigen is a widely used method to induce autoimmune disease in animal models, yet the contribution of CFA to the immune response is not well understood. We compared the effectiveness of CFA with Incomplete Freund's Adjuvant (IFA) or TiterMax Gold Adjuvant (TMax) in experimental autoimmune myocarditis (EAM) in male mice. Methods: EAM was induced in A/J, BALB/c, and IL6KO BALB/c male mice by injection of the myocarditogenic peptide in CFA, IFA, or TMax on days 0 and 7. EAM severity was analyzed by histology on day 21. In addition, specific flow cytometry outcomes were evaluated on day 21. Results: Only mice immunized with CFA and myocarditogenic peptide on both days 0 and 7 developed substantial myocarditis as measured by histology. We observed a significantly increased level of IL6 in the spleen 3 days after CFA immunization. In the spleen and heart on day 21, there was an expansion of myeloid cells in CFA‐immunized mice, as compared to IFA or TMax‐immunized animals. Recombinant IL‐6 at the time of IFA immunization partially restored susceptibility of the mice to EAM. We also treated EAM‐resistant IL‐6 knockout mice with recombinant IL‐6 around the time of the first immunization, on days −1 to 2, completely restoring disease susceptibility, showing that the requirement for IL‐6 coincides with primary immunization. Examining APC populations in the lymph node draining the immunization site evidenced the contribution of IL‐6 to the CFA‐dependence of EAM was through controlling local dendritic cell (DC) trafficking. Conclusions: CFA used with myocarditogenic peptide twice is required to induce EAM in both A/J and Balb/c mice. Although IFA and TiterMax induce antibody responses, only CFA preferentially induced autoantigen‐specific responses. CFA expands monocytes in the heart and in the spleen. IL‐6 signaling is required during short window around primary immunization to induce EAM. In addition, IL‐6 deficient mice resistance to EAM could be reversed by injecting IL‐6 around first immunization. IL‐6 expands dendritic cell and monocytic populations and ultimately leads to a robust T‐cell driven immune response in CFA immunized mice. Abstract : Complete Freund's Adjuvant (CFA) emulsified with an antigen is a widely used method to induce autoimmune disease in animal models, yet the contribution of CFA to the immune response is not well understood. We show that the ability of CFA to expand DC populations in the lymph node, monocytic populations in the spleen, as well as to induce antigen‐specific immunoglobulin production, may account for its necessity in the induction of autoimmune heart inflammation in experimental autoimmune myocarditis mouse model.